At the heart of the arterial baroreflex: a physiological basis for a new classification of carotid sinus hypersensitivity. (20th March 2013) - Wieling, W.; Krediet, C. T. P.; Solari, D.; de, F. J.; van, N.; Thijs, R. D.; van, J. G.; Brignole, M.; Jardine, D. L.
Abstract The aim of this review is to provide an update of the current knowledge of the physiological mechanisms underlying reflex syncope. Carotid sinus syncope will be used as the classical example of an autonomic reflex with relatively well‐established afferent, central and efferent pathways. These pathways, as well as the pathophysiology of carotid sinus hypersensitivity (CSH) and the haemodynamic effects of cardiac standstill and vasodilatation will be discussed. We will demonstrate that continuous recordings of arterial pressure provide a better understanding of the cardiovascular mechanisms mediating arterial hypotension and cerebral hypoperfusion in patients with reflex syncope. Finally we will demonstrate that the current criteria to diagnose CSH are too lenient and that the conventional classification of carotid sinus syncope as cardioinhibitory, mixed and vasodepressor subtypes should be revised because isolated cardioinhibitory CSH (asystole without a fall in arterial pressure) does not occur. Instead, we suggest that all patients with CSH should be thought of as being 'mixed', between cardioinhibition and vasodepression. The proposed stricter set of criteria for CSH should be evaluated in future studies.